Tumor bleeding requiring intervention and the correlation with anemia in uterine cervical cancer for definitive radiotherapy. (25th August 2018) - Yanazume, Shintaro; Karakida, Noriko; Higashi, Ryutaro; Fukuda, Mika; Togami, Shinichi; Kamio, Masaki; Ota, Shunichiro; Kobayashi, Hiroaki
Abstract : Genital bleeding during radiotherapy was associated with anemia, and is not a negligible prognostic factor in cervical cancer. Abstract: Background: The prognostic impact of tumor bleeding requiring intervention and the correlation with anemia on the survival outcome of cervical cancer radiotherapy is unclear. Methods: One hundred and ninety-six patients requiring hemostatic intervention between January 2006 and March 2014 were retrospectively investigated. The correlation between anemia and bleeding during radiotherapy, the prognostic impact of genital bleeding during radiotherapy and the influence of blood transfusion were estimated. Results: None of the patients had incomplete or prolonged treatment exceeding 1 week due to bleeding. All tumor bleeding could be controlled by gauze packing, and no patients suffered from fatal genital bleeding. Bleeding significantly correlated with progression-free survival ( P = 0.015) and overall survival ( P = 0.048). Regarding the risk factors of anemia: age ( P = 0.043), FIGO stage ( P < 0.001), tumor diameter ( P < 0.001), and bleeding ( P = 0.002) were significant. Multivariate analysis revealed FIGO stage (Odds Ratio: 2.360; 95% CI = 1.202–4.633; P = 0.013), tumor diameter (Odds Ratio: 2.089; 95% CI = 1.048–4.162; P = 0.036) and Bleeding (Odds Ratio: 2.226; 95% CI = 1.052–4.709; P = 0.036) were independent to anemia. Anemia (Hazard Ratio = 1.894; 95% CI = 1.082–3.318; P = 0.025) was only independently correlated with progression free survival, while bleeding (Hazard Ratio = 1.156; 95% CI = 0.556–2.406; P = 0.698) had no independent correlation. Blood transfusion did not improve progression-free survival in patients with anemia or genital bleeding ( P = 0.742). Conclusion: We have proved that genital bleeding requiring intervention during cervical cancer radiotherapy is a negligible prognostic factor and is the independent factor for causing anemia. Easily bleeding tumors are potential prognostic markers, which are not effectively treated using existing radiotherapy.